2019
DOI: 10.1590/s1982-21702019000s00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GNSS Indices, Ionosondes and All-Sky Imagers in Monitoring the Ionosphere in Brazil During Quiet and Disturbed Days

Abstract: Measurements from the Global Navigation Satellite System (GNSS) have become a leading data source for ionospheric studies. Different technologies are used to monitor the ionospheric layer. It is possible to carry out this monitoring using GNSS networks through the indices of ionospheric irregularities, as well as through ionosondes and imagers. It has therefore become essential to correlate these forms of monitoring, presenting their advantages and disadvantages. With this in mind, the aim of this work was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…That means if you increases the frequency of the transmitter beyond the F2-layer the radio waves will not reflected but it will be transmitted. The trace around 100km is the Elayer and foE is the critical frequency of E-layer and ℎ ′ is the virtual height of E-layer (Souza and Camargo, 2019).…”
Section: Ionosondementioning
confidence: 99%
“…That means if you increases the frequency of the transmitter beyond the F2-layer the radio waves will not reflected but it will be transmitted. The trace around 100km is the Elayer and foE is the critical frequency of E-layer and ℎ ′ is the virtual height of E-layer (Souza and Camargo, 2019).…”
Section: Ionosondementioning
confidence: 99%
“…On 6 September 2017, a X9.3 class solar flare occurred and Pereira et al (2021a) successfully proved that it was possible to use the International GNSS Service (IGS) network infrastructure to detect the event by evaluating an increase in the estimated TEC value. Souza and Camargo (2019) presented an interesting multi-instrumental study for two distinct nights, with and without records of ionospheric irregularities. Based on ionospheric irregularity indices, ionosonde data and all-sky optical imagers, the authors discussed the potential and limitations of each instrument, and confirmed the benefit of analyzing the ionosphere through the fusion of data from different sensors.…”
Section: Ionospheric Dynamics Over Brazilmentioning
confidence: 99%
“…They found that the ROTI map describes the development of the TEC irregularities and characterizes the ionospheric responses to auroral activity in both hemispheres. Souza and Camargo (2019) showed that ROTI could present the temporal evolution of ionospheric irregularities in the Brazilian sector. However, it was not possible to observe the propagation direction, generation, and evolution of the observed irregularities because the authors used one station only.…”
Section: Introductionmentioning
confidence: 99%